Uji Daya Hambat Sabun Mandi Kombucha Bunga Telang Sebagai Produk Bioteknologi Farmasi Terhadap Bakteri Shigella dysentriae dan Vibrio cholera Dari Tiga Lokasi Budidaya Bunga Telang (Pekuncen, Ciwedus, Cigeblak) - Hussein, Ahmad Saddam; Rezaldi, Firman; Herjayanto, Muh.; Yenny, Ratna Fitry; Rusmana; Humaidi, Agus (JAGO TOLIS : Jurnal Agrokompleks Tolis, 2025)
The use of herbal cosmetics is one of the lifestyles that need to be improved in order to implement back to nature. One of the pharmaceutical biotechnology products that can be developed as an antibacterial for Shigella dysentriae and Vibrio cholera made from butterfly pea flower kombucha is bath soap. The use of natural cosmetics is influenced by several factors of the cultivation location used as a sample in the scope of this study. The locations for taking samples of butterfly pea flowers in this study were Pekuncen, Ciwedus, and Cigeblak villages in Cilegon City, Banten. The three locations for cultivating the plant were used to provide information on its potential as an antibacterial in inhibiting the growth of both test bacteria. The study showed that bath soap containing the active ingredient of butterfly pea flower kombucha in each formula and three cultivation locations showed a positive correlation as a pharmaceutical biotechnology product and antibacterial against Shigella dysentriae and Vibrio cholera organisms. The optimal formula to inhibit the growth of both test microorganisms, especially those from butterfly pea flowers cultivated in Pekuncen Village, was a concentration of 40%. This is due to differences in plant cultivation locations, especially the altitude of the place producing different metabolite compound content, especially in this study as antibacterial in inhibiting the growth of both test bacteria.